Opal Lee and What it Means to be Free : The True Story of the Grandmother of Juneteenth - Duncan, Alice Faye; Bobo, Keturah A. (Nashville, Tennessee : Thomas Nelson, 2021)
"The true story of Black activist Opal Lee and her vision of Juneteenth as a holiday for everyone will inspire children to be brave and make a difference. Growing up in Texas, Opal knew the history of Juneteenth, but she soon discovered that most Americans had never heard of the holiday that represents the nation's creed of "freedom for all.""--
"The true story of Black activist Opal Lee and her vision of Juneteenth as a holiday for everyone celebrates Black joy and inspires children to see their dreams blossom. Growing up in Texas, Opal knew the history of Juneteenth, but she soon discovered that many Americans had never heard of the holiday that represents the nation's creed of "freedom for all."Every year, Opal looked forward to the Juneteenth picnic--a drumming, dancing, delicious party. She knew from Granddaddy Zak's stories that Juneteenth celebrated the day the freedom news of President Lincoln's Emancipation Proclamation finally sailed into Texas in 1865--over two years after the president had declared it! But Opal didn't always see freedom in her Texas town. Then one Juneteenth day when Opal was twelve years old, an angry crowd burned down her brand-new home. This wasn't freedom at all. She had to do something! Opal Lee spent the rest of her life speaking up for equality and unity. She became a teacher, a charity worker, and a community leader. At the age of 89, she walked from Fort Worth, Texas to Washington, D.C., in an effort to gain national recognition for Juneteenth.Through the story of Opal Lee's determination and persistence, children ages 4 to 8 will learn:all people are created equalthe power of bravery and using your voice for changethe history of Juneteenth, or Freedom Day, and what it means todayno one is free unless everyone is freefighting for a dream is worth every difficultyFeaturing the illustrations of New York Times bestselling illustrator Keturah A. Bobo (I am Enough), Opal Lee and What It Means to Be Free celebrates the life and legacy of a modern-day Black leader while sharing a message of hope, unity, joy, and strength"--
Includes bibliographical references.
Keywords: Lee, Opal, -- 1926-; Juneteenth -- Juvenile literature; African American women civil rights workers -- Juvenile literature. -- Texas; African Americans -- Juvenile literature. -- Anniversaries, etc; Slaves -- Juvenile literature. -- Emancipation -- Texas; African Americans -- Juvenile literature. -- Social life and customs; African Americans -- Juvenile literature. -- History -- Texas; JUVENILE NONFICTION / Biography & Autobiography / Social Activists; JUVENILE NONFICTION / Holidays & Celebrations / Patriotic Holidays